CHANGING CLINICAL PROFILE OF ACUTE RHEUMATIC FEVER AND RHEUMATIC RECURRENCE - Sheikh, Abdul Malik; Sadiq, Masood; Rehman, Asif Ur (Journal of Ayub Medical College Abbottabad, 2016)
Background: Clinical profile of acute rheumatic fever and rheumatic recurrence seems to have changed in countries where rheumatic fever is still endemic. The objectives of this study were to compare clinical profile and outcome of patients suffering initial and recurrent episodes of acute rheumatic fever in children. Methods: This prospective study was conducted in two tertiary care hospitals from January to June 2011. The diagnosis was based on the modified Jones criteria. Sixty children were included in the study, 15 having first episode of rheumatic fever and 45 with rheumatic recurrence. The severity of carditis was assessed by Clinical and echocardiography means. Results: Carditis was the commonest presentation in both first (80%) and recurrent attacks (100%). Arthritis was seen in 60% of children with first episode and in 26.7% with recurrence. The frequency of subcutaneous nodules, invariably associated with carditis, was very high (33.3% in the first and 48.3% in recurrent episodes). Carditis was generally mild during first episode (53.3%) and severe with rheumatic recurrence (55.6%). There was no death in either group. One patient with severe mitral regurgitation and rheumatic recurrence underwent mitral valve repair for intractable heart failure. Conclusion: Clinical profile of rheumatic recurrence and acute rheumatic fever has changed. Rheumatic recurrence is associated with severe carditis. Carditis is more common than arthritis even in the first attack. Sub-cutaneous nodules are a frequent finding invariably associated with carditis.